Revenue Automation Enhancing Operational Efficiencies and Financial Tools for CROs and Clinical Sites - Rama Rao; Enrico Perfler (Blockchain in Healthcare Today, 2025)
This ConV2X 2024 fireside chat delves into the critical financial challenges faced by CROs and sites, including delayed payments, unpredictable cash flows, and the impact of inflation on long-term contracts.